Penerapan Standard Operational Procedure Check-In dan Check-Out Tamu Individual Di Hotel Horison Ultima Seminyak - Putu Setia Priyatna Putra Setia; Ni Luh Putu Sri Widyastuti; Ida Ayu Karina Putri (HARMONY HOSPITALITY, 2025)
This study aims to examine the implementation of Standard Operating Procedures (SOPs) in the check-in and check-out process for individual guests by receptionists at the Horison Ultima Hotel Seminyak. As a star-rated hotel, consistent implementation of standard operating procedures (SOP) is crucial to ensure service quality and create a positive guest experience. Receptionists play a crucial role as they are at the forefront of welcoming guests, confirming reservations, providing information regarding hotel facilities, and ensuring smooth administration during the check-in and check-out process. This study used a qualitative approach with observation and in-depth interviews with receptionists. The results showed that, in general, receptionists have implemented SOPs well, starting from verifying guest identity, filling out registration forms, to handling payments and deposit refunds. However, several obstacles were found such as lack of consistency in providing information to guests and delays in the check-out process during peak hours, as well as frequent errors during the check-in process such as delays in the check-in process which resulted in dissatisfaction of guests who wanted to stay and gave rise to negative comments that could make the hotel's image less good, therefore the receptionist must implement the established standard operating procedure (SOP) in order to ensure optimal service. Therefore, the receptionist must understand and always implement the established standard operating procedure in the hotel correctly, because the receptionist is the face of the hotel that guests see first when staying at the hotel, and provide a positive experience for guests who want to stay at the hotel.